Elements to Be Considered Prior to Summoning the Employee to a Disciplinary Investigation. Establishment of Disciplinary Misconduct Committed by the Employee and the Conditions for Disciplinary Liability - Mihaela Emilia Marica (Perspectives of Law and Public Administration, 2023)
Given the mandatory nature of the preliminary disciplinary investigation procedure, this disciplinary process to which employees are submitted can be divided into three main phases, namely the phase prior to the employee's summoning, the moment of the employee's hearing and the phase following employee's investigation. Clarity on these stages and the proceedings corresponding to each of them, is essential for the validity of the disciplinary sanction. As the disciplinary process is complex both in terms of the current regulatory framework and judicial practice, the present article addresses some aspects of the preliminary disciplinary investigation procedure, with special focus on the problems identified in the phase prior to the employee's summoning to the disciplinary investigation. We will consider both descriptive technical elements and elements that generate significant divergences or controversy over practical matters. The comparative law elements presented will also highlight how other legal systems regulate issues relating to the procedure for imposing disciplinary sanctions. The legal regulations of Bulgaria, the United Kingdom, Cyprus, New Zealand are presented.